Functional Outcome and Complication Rates of External Fixation Versus Internal Fixation in Open Fractures - TANVIR, IMRANA (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Open fractures are severe orthopedic injuries that result in substantial soft tissue trauma, increased risk of infection, prolonged healing time, and poor long-term function. Whether to use external fixation or internal fixation is still controversial, especially in terms of complications and restoration of limb function. Objective: To assess the functional and complications rates of external fixation and internal fixation in patients with open fractures. Methods: This prospective comparative clinical study was carried out in the Department of Orthopedic Surgery of a tertiary care teaching hospital between February 2024 and February 2025. Seventy adult patients with radiologically diagnosed open fracture of long bones were enrolled by non-probability consecutive sampling. The participants were divided into two groups of 35 each based on the type of fixation: external fixation and internal fixation. Demographic and injury characteristics were documented and fracture type was assessed using the Gustilo-Anderson classification. At follow-up, functional assessment was performed using the Lower Extremity Functional Scale (LEFS), Disability of the Arm, Shoulder and Hand (DASH) score and clinical grading. The two groups were compared for complications such as infection, delayed union, non-union, malunion, implant or fixation failure, and joint stiffness. Results: Internal fixation demonstrated better overall functional recovery, with a greater proportion of patients achieving excellent or good outcomes compared with external fixation. Functional outcome scores were better in the internal fixation group. The external fixation group had a higher incidence of superficial infection, pin tract infection, delayed union and joint stiffness, while the incidence of deep infection was higher in the internal fixation group. Both groups experienced non-union and implant failure with a slight difference. Conclusion: Internal fixation had better functional results, while external fixation was still a safe and effective treatment for more severe open fractures with poor soft tissue conditions.